Perceived Knowledge and Attitude of Fisheries Extension Professionals on Usage of ICTs in Tripura - Nirmalkar, Chandrashekhar; Lahiri, Biswajit; Ghsoh, Amitava; Pal, Prasenjit; Baidya, Sampa; Shil, Bikash; Kurmi, Ram Kumar (Indian Journal of Extension Education, 2025)
Applications of Information and Communication Technologies (ICTs) offer excellent possibilities for strengthening transfer of technology between research and extension systems and onward transmission to the end-users. The study aims at studying the perceived knowledge and attitude levels of fisheries extension professionals of Tripura on the usage of ICTs concerning their socio-personal characteristics and explores the associated challenges. Data were gathered by pre-tested semi-structured interview schedule from completely enumerated 81 extension professionals of the department of fisheries, posted in the three purposively selected districts of Tripura during April- August 2021. The majority of respondents belonged to the middle age group (61.73%) and had medium level knowledge (78.57%) and attitude (85.18%) towards the use of ICT tools. Age and designation were negatively correlated, whereas education was positively and significantly correlated with knowledge and attitude level of fisheries extension professionals on usage of ICT tools separately. The Directorate of Fisheries of the state should develop meticulous strategies for each level of fisheries extension professionals to address the main challenges related to the use of ICT tools revealed in the study, which may bring a paradigm shift in fisheries farm information communication.